„Gesagt. Getan.“: Der Handlungsaspekt des persuasiven Diskurses im National- sozialismus unter argumentationsanalytischem Blickwinkel - Danler, Paul (Linguistik Online, 2019)
An orator tries to turn his/her personal point of view into a generally accepted one using a variety of rhetorical means; one of which is argumentation. However, since the relationship between rhetoric and argumentation is somewhat controversial, I will first of all try to identify the role of argumentation within rhetoric. After that, I will briefly discuss the nature of a wide range of argumentation schemes. Arguments have been classified in different ways. One very convincing and effective way is that suggested by Kienpointner. I will present his typology, which will afterwards serve as basis for my empirical analysis of an important speech given by Hitler on February 1st, 1933. I have identified ten groups of argumentative structures in this speech, which will be discussed and illustrated by numerous examples.My main concern of the analysis is the pragmatic aspect of the political speech. The key question is what changes for the audience after listening to that speech? The audience gets new information or maybe familiar information but from a new point of view, and this will have some influence on the audience’s future outlook.